PassGuard: Password Manager with Unauthorized Access Detection - Mohamed Shaharudeen, Ahmad Amirul Aiman; RAHIM, NORDIANA (Applied Information Technology And Computer Science, 2026)
PassGuard is designed to address concerns about the security and management of sensitive information. It offers a secure, user-friendly password manager to store and organize credentials, secure notes, payment details, and more. With features like a built-in password generator and TrustGuard for improving password strength, it provides comprehensive protection. The application tackles the risks of password theft and unauthorized access by implementing OTP-based validation and intrusion detection, including real-time alerts with OpenCV. Built using Python and PyQt5, PassGuard is intended for Windows users. Its core functionalities, including account registration, recovery mechanisms, and advanced security controls, have undergone structured user acceptance testing (UAT) to validate usability, reliability, and effectiveness across a range of real-world scenarios. This ensures secure storage, streamlined access, and proactive threat detection to enhance digital safety.